1986
DOI: 10.1177/0306624x8603000107
|View full text |Cite
|
Sign up to set email alerts
|

Angry Women Offenders: Case Study of a Group

Abstract: This article explains the development and rationale for a therapeutic group with female offenders which provided a climate for exploring anger. A multi-faceted approach was utilized to assist women offenders in a maximum security prison learn to acknowledge, accept, and constructively release their anger. Outcomes included increased personal control, responsibility, and empathy. Other outcomes included an increased ability to generate and utilize alternatives which led to much more flexible, creative, and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Research in the jail setting often has added institutional safeguards to protect detainee rights and to provide assurance that the research will benefit the prisoners (Brakel, 1996). In spite of these barriers, the jail setting has been demonstrated to be a viable place for both treatment intervention and research into growing clinical, public health, and societal problems (El-Bassel et al, 1995Peyrot et al, 1994;Teplin et al, 1996Teplin et al, , 1997Wilfley et al, 1986). More resources need to be directed toward comprehensive services and research into treatment effectiveness to stem the tide of the growing mental health and public health problems that account for the increasing criminal and psychiatric recidivism among female offenders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in the jail setting often has added institutional safeguards to protect detainee rights and to provide assurance that the research will benefit the prisoners (Brakel, 1996). In spite of these barriers, the jail setting has been demonstrated to be a viable place for both treatment intervention and research into growing clinical, public health, and societal problems (El-Bassel et al, 1995Peyrot et al, 1994;Teplin et al, 1996Teplin et al, , 1997Wilfley et al, 1986). More resources need to be directed toward comprehensive services and research into treatment effectiveness to stem the tide of the growing mental health and public health problems that account for the increasing criminal and psychiatric recidivism among female offenders.…”
Section: Discussionmentioning
confidence: 99%
“…Although still relying on self-reports, these studies demonstrated improved social and emotional adjustment and fewer physical complaints among women in the treated group in comparison with nonparticipants. Wilfley, Rodon, and Anderson (1986) reported positive results with an anger exploration program for mentally ill female offenders in maximum security. The main purpose of the program was to provide offenders with an opportunity to gain awareness and understanding of their anger and to develop appropriate methods for managing it.…”
Section: Treatment Programs For Female Detaineesmentioning
confidence: 99%
“…Although anger management programs are offered to female offenders, they typically do not differ from men's programs, however, sex differences in anger expression suggest the need for gender-specific programs (Suter & Byrne, 2000). Only four such programs have been reported in the literature (Cundy, 1995, as cited in Horn & Towl, 1997Rucker, 1991, as cited in Crump, 1995Smith, Smith & Beckner, 1994;Wilfley, Rondon, & Anderson, 1986). Although group goals varied, in general, they emphasised anger awareness; management strategies; and occasionally, the identification of social causes of anger (e.g., gender-related learning and life stressors).…”
Section: Treatment Needs Of Female Offendersmentioning
confidence: 99%
“…Although group goals varied, in general, they emphasised anger awareness; management strategies; and occasionally, the identification of social causes of anger (e.g., gender-related learning and life stressors). All groups reported some success including increases in personal control (Rucker, 1991, as cited in Crump, 1995Wilfley et al, 1986), responsibility, empathy, self-perception, and utilisation of appropriate alternatives to anger (Smith et al, 1994;Wilfley et al, 1986), as well as increases in friendship and support networks between participants (Cundy, 1995, as cited in Horn & Towl, 1997;Wilfley et al, 1986). However, more empirical work is required, particularly in developing more intensive programs (preferably 100 hours plus) that address interconnected mental health issues -brief interventions are insufficient and unlikely to produce enduring gains.…”
Section: Treatment Needs Of Female Offendersmentioning
confidence: 99%
“…The high percentages in prison for violent offenses may serve to justify the increasing tendency to offer anger management as a part of prison treatment programs for both males and females (Smith and Beckner, 1993;Wilfrey, Rodon, and Anderson, 1986). The high concentration of violent inmates, and the increasing tendency to offer anger management programs both suggest that a reliable tool for measuring anger would be of some use, particularly if it had demonstrated predictive power.…”
Section: Introductionmentioning
confidence: 99%